Prevenção de comportamentos agressivos entre pré-escolares: uma proposta de capacitação para professores. - Luizzi, Luciana (2006)
Literature about childish aggressiveness has evidenced importance of schools prepare to cope with aggressive students more effectively, that demand a lot of teachers instructional and behavior management skills. The continuation of punitive practices, used in schools, can be result of teachers lack of skill to cope with children who show aggressive behavior. Otherwise that, application of proper behavior management strategies and the development of positive relationships among teachers and children contribute to promote social and academic success, especially to children at risk. Several authors have argued a comprehensive intervention applied in the preschool is the more effective method to divert these children of antisocial pathway. Necessary conditions in the school context to support teachers to cope with aggressive children have been the object of several researches. International literature has indicated positive effects by the application of intervention programs in the school context on aggressive behavior. These effects are: the decrease of aggressive behavior rate and improvements social and academic skills in children, and the teachers acquisition of skills to cope with aggressive children. It was verify the necessity of identify characteristics relative to teacher s role in intervention programs, referring to knowledge and skills required to support students, and relative to teaching strategies that are offered to teacher act properly. The present research intended to elaborate a capability proposal, derivative of successful school-based intervention programs revision, that promote the improvement of teachers skills, directed to prevent and/or minimize preschoolers aggressive behaviors. Method was divided in four stages: (1) search and identification of successful school intervention programs; (2) a wide description of each intervention program; (3) a specific description of skills and tasks that are related to participants and responsible professionals performance in the programs; and (4) the elaboration of a capability proposal for the improvement of teacher skills in coping with aggressive preschoolers. The main results consisted in four products: (a) identification of relevant skills to be developed by students; (b) identification of proper strategies to development of these skills; (c) proposition of a set of the teachers skills required toward implement teaching strategies which aim at prevention of aggressive behavior in classroom; and (d) proposition of conditions to be offered toward teachers. The aim of this study is to make available a capability proposal to preschool teachers, based on successful theoretical and experimental foundations provided by programs described in the literature. This product is considered to be important in the development of future investigations on the necessary teaching conditions related to the improvement of teachers skills in coping with children who exhibit aggressive behavior problems.